Moral Analysis in The Animated Film of Adit Sopo Jarwo as Educational Shows (Jurnal Sustainable, 2023)
The authors intend to analyze and describe the moral and educational values contained in the Adit and Sopo Jarwo animation series in this journal. The research method used in this journal is qualitative with a descriptive approach, and the sample used in this study is the Adit and Sopo Jarwo title series with content analysis techniques. The data in this study are in the form of religious and moral values obtained from the Adit and Sopo Jarwo animation series. Moral values such as eating manners, patience and honesty manners, consistent manners when working, responsible manners, helping etiquette, and forgiveness. In addition, there are traditional Indonesian games in the animation, with the goal of not being forgotten by traditional Indonesian games. As a result, the animated series Adit and Sopo Jarwo is highly recommended for children to watch because it can help them develop positive moral and religious values.